PTH-075 Predictors of Post-Operative Recurrence of Ileal Crohn's Disease. (17th August 2016) - Quraishi, MN; Widlak, M; Bhala, N; Sharma, N; Iqbal, TH
Abstract : Introduction: Long term follow up of patients resected for ileal Crohn's (IC) disease have reported recurrence rates to range from 10–30% during the first post-operative year. Recent randomised controlled trials have shown that the "treat to target" approach based early colonoscopy to detect and treat early recurrence is crucial in maintaining remission. This study aims to identify clinical factors that predict risk of recurrence to help stratify patients that warrant early colonoscopy. Methods: In a retrospective study conducted in a University Hospital with a catchment area of 1 million patients, clinical records of patients with Crohn's disease under regular follow-up from January 2011 to November 2013 were reviewed to identify patients who underwent ileal resection. The outcome after surgery was assessed on the basis of electronic patient records that were prospectively followed up till November 2015. Results: 50 patients were included in this study (median age: 34 years, male: 21 (42%)). The median duration of postoperative follow-up was 22 months. 26 (52%) patients had endoscopic or radiological evidence of recurrent disease. Probabilities of recurrence according to the Kaplan-Meier method were 22% and 41% at 1 and 2 years respectively. Univariate analysis (log-rank) showed that pre-operative dual immunosuppression with immunomodulatory and biological agents (p = 0.01), lack of response pre-operatively to at least two biological agents (p = 0.01) and previous surgery (p = 0.02) were associated with increased risk of recurrence of IC disease. Multivariate Cox hazard model demonstrated that fibrostenotic or fistulating/penetrating disease (HR = 3.55; 95% CI 1.24 to 10.19; p = 0.02), perianal disease (HR = 2.41; 95% CI 1.02 to 5.66; p = 0.04) and smoking (HR = 2.92; 95% CI 1.18 to 7.22; p = 0.02) significantly increased risk of recurrence post ileal resection and were independent predictors of relapse. Older age at diagnosis non-significantly reduced the risk of post-operative recurrence of IC disease (HR = 0.53; 95% CI 0.25 to 1.09; p = 0.086). Conclusion: In addition to known risk factors we have shown that patients on dual immunosuppression and failure of two biologics pre-operatively are significant factors in predicting early recurrence. In the era of "treat to target" approach to achieve mucosal healing and sustained remission, risk stratification based on strong clinical predictors of early post-operative recurrence of Crohn's disease will help guide timing of colonoscopy following surgery. Disclosure of Interest: None Declared